Formation of environmental competence of future specialists in pedagogical universities - Маликқызы, Лаура; Жанбеков, Хайрулла; Роговая, Ольга (Pedagogy and Psychology, 2020)
Environmental education and upbringing is one of the important tasks of training young professionals. Today, every young specialist becomes a competent, competent person in their profession, and environmental competence is formed in the University and in matters of postgraduate education. In this context, it is stated that students of the specialty chemistry and biology, along with the main basic disciplines, increase the teaching of specialized disciplines. As a result of testing the expertise: the value of environmental competence is determined, the need for the formation of which was noted in the conditions that provide high-quality training of specialists of a pedagogical University to practice by forming its environmental consciousness.It was found that students in conducting experimental research on environmental problems, in combination with theory, can cause environmental and pedagogical competence.